Long-Time Trends in Night Sky Brightness and Ageing of SQM Radiometers - Pietro Fiorentin; Renata Binotto; Stefano Cavazzani; Andrea Bertolo; Sergio Ortolani; Ivo Saviane (Remote Sensing, 2022)
A very wide-used instrument for the measurement of the Night Sky Brightness (NSB) is the Sky Quality Meter (SQM). One of its important issues is tracking NSB for long time and connecting its variations to changes in outdoor lighting. The stability of these radiometers is fundamental; variation on the instrument behaviour could be confused with changes of the sky brightness. The SQMs of the network of the Veneto Region (Italy) and the SQM installed at La Silla (Chile) are analysed by using the twilight method considering both sunset and dawn measurements, which allows to compensate for shifts in the SQM internal clock. The slope of the observed long-term trends ranges between 29 ± 5 and 86 ± 22 mmagSQM arcsec−2 year−1. These high values require a correction of the measurements to continue to track NSB by those instruments. The correction is presented for an Italian site, for example: raw measures show an apparent trend towards darker sky (30 ± 5 mmagSQM arcsec−2 year−1), after the correction a clear tendency towards a brighter polluted sky appears (−21 ± 8 mmagSQM arcsec−2 year−1), in agreement with the estimated trend of the installed luminous flux of outdoor lighting for that area.